Notes on the Underground: Monetary Policy in Resource-Rich Economies - Andrea Ferrero; Martin Seneca (Norges Bank, 2015)
How should monetary policy respond to a commodity price shock in a resource-rich economy? We study optimal monetary policy in a simple model of an oil exporting economy to provide a first answer to this question. The central bank faces a trade-off between the stabilization of domestic inflation and an appropriately defined output gap as in the reference New Keynesian model. But the welfare-relevant output gap depends on oil technology, and the weight on output stabilization is increasing in the size of the oil sector. Given substantial spillovers to the rest of the economy, optimal policy therefore calls for a reduction of the interest rate following a drop in the oil price in our model. In contrast, a central bank with a mandate to stabilize consumer price inflation may raise interest rates to limit the inflationary impact of an exchange rate depreciation.
hdl:11250/2495872
Keywords: E52; E58; J11; 330; small open economy; oil export; monetary policy